Functional Genomics and Phylogenetic Evidence Suggest Genus-Wide Cobalamin Production by the Globally Distributed Marine Nitrogen Fixer Trichodesmium - Walworth, Nathan G.; Lee, Michael D.; Suffridge, Christopher; Qu, Pingping; Fu, Fei-Xue; Saito, Mak A.; Webb, Eric A.; Sañudo-Wilhelmy, Sergio A.; Hutchins, David A. (Frontiers in Microbiology, 2018)
Only select prokaryotes can biosynthesize vitamin B12 (i.e. cobalamins), but these organic co-enzymes are required by all microbial life and can be vanishingly scarce across extensive ocean biomes. Although global ocean genome data suggest cyanobacteria to be a major euphotic source of cobalamins, recent studies have highlighted that >95% of cyanobacteria can only produce a cobalamin analog, pseudo-B12, due to the absence of the BluB protein that synthesizes the  ligand 5,6-dimethylbenzimidizole (DMB) required to biosynthesize cobalamins. Pseudo-B12 is substantially less bioavailable to eukaryotic algae, as only certain taxa can intracellularly remodel it to one of the cobalamins. Here we present phylogenetic, metagenomic, transcriptomic, proteomic, and chemical analyses providing multiple lines of evidence that the nitrogen-fixing cyanobacterium Trichodesmium transcribes and translates the biosynthetic, cobalamin-requiring BluB enzyme. Phylogenetic evidence suggests that the Trichodesmium DMB biosynthesis gene, bluB, is of ancient origin, which could have aided in its ecological differentiation from other nitrogen-fixing cyanobacteria. Additionally, orthologue analyses reveal two genes encoding iron-dependent B12 biosynthetic enzymes (cbiX and isiB), suggesting that iron availability may be linked not only to new nitrogen supplies from nitrogen fixation, but also to B12 inputs by Trichodesmium. These analyses suggest that Trichodesmium contains the genus-wide genomic potential for a previously unrecognized role as a source of cobalamins, which may prove to considerably impact marine biogeochemical cycles.